Negative- versus positive-pressure ventilation in intubated patients with acute respiratory distress syndrome - Raymondos, Konstantinos (BioMed Central, 2012)
INTRODUCTION: Recent experimental data suggest that continuous external negative-pressure ventilation (CENPV) results in better oxygenation and less lung injury than continuous positive-pressure ventilation (CPPV). The effects of CENPV on patients with acute respiratory distress syndrome (ARDS) remain unknown. METHODS: We compared 2 h CENPV in a tankrespirator ("iron lung") with 2 h CPPV. The six intubated patients developed ARDS after pulmonary thrombectomy (n = 1), aspiration (n = 3), sepsis (n = 1) or both (n = 1). We used a tidal volume of 6 ml/kg predicted body weight and matched lung volumes at end expiration. Haemodynamics were assessed using the pulse contour cardiac output (PiCCO) system, and pressure measurements were referenced to atmospheric pressure. RESULTS: CENPV resulted in better oxygenation compared to CPPV (median ratio of arterial oxygen pressure to fraction of inspired oxygen of 345 mmHg (minimum-maximum 183 to 438 mmHg) vs 256 mmHg (minimum-maximum 123 to 419 mmHg) (P < 0.05). Tank pressures were -32.5 cmH(2)O (minimum-maximum -30 to -43) at end inspiration and -15 cmH(2)O (minimum-maximum -15 to -19 cmH(2)O) at end expiration. NO Inspiratory transpulmonary pressures decreased (P = 0.04) and airway pressures were considerably lower at inspiration (-1.5 cmH(2)O (minimum-maximum -3 to 0 cmH(2)O) vs 34.5 cmH(2)O (minimum-maximum 30 to 47 cmH(2)O), P = 0.03) and expiration (4.5 cmH(2)O (minimum-maximum 2 to 5) vs 16 cmH(2)O (minimum-maximum 16 to 23), P =0.03). During CENPV, intraabdominal pressures decreased from 20.5 mmHg (12 to 30 mmHg) to 1 mmHg (minimum-maximum -7 to 5 mmHg) (P = 0.03). Arterial pressures decreased by approximately 10 mmHg and central venous pressures by 18 mmHg. Intrathoracic blood volume indices and cardiac indices increased at the initiation of CENPV by 15% and 20% (P < 0.05), respectively. Heart rate and extravascular lung water indices remained unchanged. CONCLUSIONS: CENPV with a tank respirator improved gas exchange in patients with ARDS at lower transpulmonary, airway and intraabdominal pressures and, at least initially improving haemodynamics. Our observations encourage the consideration of further studies on the physiological effects and the clinical effectiveness of CENPV in patients with ARDS.